Friction stir welding of dissimilar stainless steels: evaluation of flow pattern, microstructure and mechanical properties. (6th February 2019) - Guo, Guolin; Shen, Yifu
Abstract: The friction stir welded joints of austenitic and ferritic stainless steels were implemented at different rotational speeds 700∼900 rpm. The results indicated that the heat input and the material flow in welded zone were improved with increasing rotational speed, and the nugget zone presented blocky, laminated and vortex structure of austenite and ferrite. The joining mechanism transformed from simple mechanical mixing to combination of mechanical and metallurgical connections, proved by the Ni element diffusion at the interface of austenite and ferrite matrix. A reliable joint with the maximum tensile strength was achieved by two-phase laminated structure performed at rotational speed 800 rpm. The fracture occurred in the thermo-mechanically affected zone on the advancing side. The grains of the stir zone were refined from 20 μ m to 2 μ m by dynamic recrystallization.